2023
DOI: 10.1186/s13020-023-00814-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrating animal experiments, mass spectrometry and network-based approach to reveal the sleep-improving effects of Ziziphi Spinosae Semen and γ-aminobutyric acid mixture

Airong Ren,
Tingbiao Wu,
Yarong Wang
et al.

Abstract: Background Ziziphi Spinosae Semen (ZSS) is a plant widely used as medicine and food in Asian countries due to its numerous health benefits. γ-aminobutyric acid (GABA), a non-proteinaceous amino acid, is one of the major inhibitory neurotransmitters with a relaxant function. In this study, a system pharmacology approach was employed to assess the effects of a mixture composed of ZSS and GABA (ZSSG) on sleep improvement. Methods Mice were divided int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…To construct a network involving drug targets and disease‐related proteins, we first mapped the ingredient target proteins and ALD proteins to the human interaction network. Subsequently, we extracted a sub‐network to generate the drug–disease subgraph utilizing the Python NetworkX package, as previously described (Airong Ren et al., 2024 ; Ren et al., 2023 ). The extracted node and edge lists were subsequently imported into Gephi software (version 0.9.2) to generate a comprehensive drug–disease diagram.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To construct a network involving drug targets and disease‐related proteins, we first mapped the ingredient target proteins and ALD proteins to the human interaction network. Subsequently, we extracted a sub‐network to generate the drug–disease subgraph utilizing the Python NetworkX package, as previously described (Airong Ren et al., 2024 ; Ren et al., 2023 ). The extracted node and edge lists were subsequently imported into Gephi software (version 0.9.2) to generate a comprehensive drug–disease diagram.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the samples were centrifuged at 4000× g for 20 min. The supernatant was characterized by a Waters Ultra‐High‐Performance Liquid Chromatography‐Quadrupole/Time‐of‐Flight–Tandem Mass Spectrometry (UPLC‐Q/TOF–MS/MS), as previously described (Ren et al., 2024 ; Ren et al., 2023 ). Chromatographic separation was performed on a Waters Acquity™ UPLC system using an ACQUITY UPLC BEH C18 column.…”
Section: Methodsmentioning
confidence: 99%
“…When the Z-Score < -1.5 and p ≤ 0.05, the TCM ingredients were considered to have a pharmacologic action. For more details, please refer to our previous research [19,20].…”
Section: Calculation Of Network Proximity 26 Protein-protein Interact...mentioning
confidence: 99%
“…By screening through a tobarbital-induced sleep test in a mouse model, it was reported that R. multiflora volved in changes in sleep latency and duration [54]. In addition, in the case of Z. j seeds and walnut peptide, it was reported that the combined use of GABA improves quantity by inducing changes in neurotransmission through pentobarbital-induced test, molecular biological techniques, and ultra-high performance liquid chrom raphy-mass spectrometry analysis [55,56]. In addition, the analysis of sleep latency duration reported differences in sleep-promoting effects depending on the type of le The effects of exposure to Z. jujuba, D. longan, and L. sativa extracts and mixed extracts on changes in sleep-related behavior in fruit flies were validated using ICR-mice, a vertebrate animal (Figure 7).…”
Section: Effects Of Z Jujuba D Longan and L Sativa Extracts And Mixed...mentioning
confidence: 99%
“…By screening through a pentobarbital-induced sleep test in a mouse model, it was reported that R. multiflora is involved in changes in sleep latency and duration [54]. In addition, in the case of Z. jujuba seeds and walnut peptide, it was reported that the combined use of GABA improves sleep quantity by inducing changes in neurotransmission through pentobarbital-induced sleep test, molecular biological techniques, and ultra-high performance liquid chromatographymass spectrometry analysis [55,56]. In addition, the analysis of sleep latency and duration reported differences in sleep-promoting effects depending on the type of lettuce and is also used as a tool to verify expected active ingredients [38,50].…”
Section: Effects Of Z Jujuba D Longan and L Sativa Extracts And Mixed...mentioning
confidence: 99%